Pengembangan Modul Pembelajaran IPA Berbasis Entrepreneurship di SMK Negeri 2 Kota Jambi - Sica Septyenthi; Aprizal Lukman; Upik Yelianti (Universitas Jambi, 2014)
Vocational high school consists of face-to-face learning and dual education system. Learning and dual education system may be either industrial work practices held for 3 or 6 months.During dual education system students can not attend face-to-face learning teaching material that students need to be able to learn independently. Specifically, learning science that students need to learn about the environment and its benefits for students.The purpose of this research is to develop instructional materials in the form of science module which helps students to learn independently and determine the response of vocational students to the science learning modules. Modules developed based entrepreneurship and contextual material with real life needs or students. The material presented is structured to support student entrepreneurship in order to be fit for purpose namely vocational work. This module development research design using the design development of Richey and Klein with Dick and Carey model for the development phase of the module material. Results of test responses of teachers and students concluded that the module gets a very good response, interesting and appropriate to the needs of students. Then the module materials can help students cultivate skills become entrepreneurs.